PENGARUH PENGGUNAAN METODE HYPNOTEACHING DALAM MENINGKATKAN KETERAMPILAN MENULIS CERPEN KELAS V UPTD SD NEGERI 44 BARRU - Abidah Idrus, Nur; Yusnadi; Alninda Rahmasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of the hypnoteaching method on the short story writing skills of fifth grade students of UPTD SD Negeri 44 Barru. This study uses a quantitative approach with a quasi-experimental research type, and a nonequivalent control group design. The subjects of the study consisted of two classes, namely the experimental class that received treatment with the hypnoteaching method, and the control class that did not receive treatment with the hypnoteaching method. Data collection techniques include short story writing tests, observations of learning implementation, and documentation. Data were obtained through pretests and posttests which were analyzed to see the improvement in short story writing skills. Based on the results of the study, it shows that there is an increase in short story writing skills in students who learn using the hypnoteaching method.